2005
DOI: 10.1016/j.otohns.2005.05.654
|View full text |Cite
|
Sign up to set email alerts
|

Association of Reflux With Otitis Media in Children

Abstract: We replicated the finding of pepsin/pepsinogen in middle ear fluid of children with OME or ROM, but did not find any increase in GER symptoms. Further research is needed to establish a causative link between GER and OM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 19 publications
6
83
0
8
Order By: Relevance
“…And these findings are in agreement with a study that investigated the causal relationship of GERD and OME by confirming the finding of pepsin/pepsinogen in the middle ear fluid of children undergoing myringotomy and tube placement for chronic or recurrent OM , and querying parents about symptoms that suggest the presence of GERD in these children [11]. Our study reported that there were significant difference between group with pepsinogen in the middle ear and group without regarding GER disorders.…”
Section: /3supporting
confidence: 92%
See 1 more Smart Citation
“…And these findings are in agreement with a study that investigated the causal relationship of GERD and OME by confirming the finding of pepsin/pepsinogen in the middle ear fluid of children undergoing myringotomy and tube placement for chronic or recurrent OM , and querying parents about symptoms that suggest the presence of GERD in these children [11]. Our study reported that there were significant difference between group with pepsinogen in the middle ear and group without regarding GER disorders.…”
Section: /3supporting
confidence: 92%
“…The patients were chosen from outpatient clinic of Otorhinolaryngology, Menoufia University Hospital with mean age 6.44±1.72 years the minimum was 4 years and maximum was 9 years. Male represent 56% (14) of the studied group and female 44% (11). A written consent was taken from the parents of all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Pepsinogen isoenzymes are found in the lung, pancreas, prostate, and some malignant tissues. Liu et al [18] found no pepsinogen 1 mRNA in infected mastoid mucosa by RT-PCR. Tasker et al [2] found no evidence of pepsinogen production by immunohistochemical methods in middle ear biopsy specimens.…”
Section: Correlation Among Pepsinogen Levels In Middle Ear Fluid and mentioning
confidence: 98%
“…Lieu et al [18] examined fluid samples obtained from 36 middle ears of 22 children. The samples were subjected to ELISA, and proteolytic activity was evaluated.…”
Section: Correlation Among Pepsinogen Levels In Middle Ear Fluid and mentioning
confidence: 99%
“…
, Elizângela Dias Camboim (5) RESUMO Tema: achados audiológicos e linguagem em gêmeas regurgitadoras. Procedimentos: o estudo consiste no relato dos achados audiológicos e do desenvolvimento da linguagem de duas crianças, irmãs gêmeas regurgitadoras.
…”
unclassified